2004
DOI: 10.1088/0953-2048/17/3/024
|View full text |Cite
|
Sign up to set email alerts
|

Details of the thermodynamical derivation of the Ginzburg–Landau equations

Abstract: We examine the procedure of thermodynamical derivation of the Ginsburg-Landau equation for current, which is given unclear and contradictory interpretations in existing textbooks. We clarify all steps of this procedure and find as a consequence a limitation on the validity range of the thermodynamic Ginsburg-Landau theory, which does not seem to be explicitely stated up to now: we conclude that the thermodynamic theory is applicable only to a superconducting specimen that is not a part of an external current-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…However, such a problem needs careful study as it is shown in ref. [22]. It was shown that the free energy variation depends on whether the variation is going with respect to the vector potential A or with respect to the magnetic field itself.…”
Section: Parallel Critical Field In Hts Thin Filmmentioning
confidence: 99%
“…However, such a problem needs careful study as it is shown in ref. [22]. It was shown that the free energy variation depends on whether the variation is going with respect to the vector potential A or with respect to the magnetic field itself.…”
Section: Parallel Critical Field In Hts Thin Filmmentioning
confidence: 99%
“…The second term in (5) is the energy difference between the normal state and the superconducting phase which is expanded in even powers in the complex 'order-parameter wave function' Ψ( r),…”
Section: Condensation Energymentioning
confidence: 99%
“…The usual expression for the coupling between condensate and vector potential involves the absolute square of the gauge-invariant gradient [1,[3][4][5][6][7][8]; the original Ginzburg-Landau functional and the corresponding boundary conditions are treated with mathematical rigor in [9].…”
Section: Kinetic Energymentioning
confidence: 99%
See 2 more Smart Citations